Examining Pragmatic Features in Tiktok Live Advertisement: A Case Study of Direct Selling Practices - Natrio, Yeyep; Lestari, Rinda (ARRUS Journal of Social Sciences and Humanities, 2024)
This study explores pragmatic strategies in Tiktok Live advertisements to understand how sellers influence consumer purchasing decisions through direct sales. Employing a qualitative approach and a case study design, data were collected from two Tiktok Live ad videos featuring apparel and bags. The analysis focused on observing interactions between sellers and viewers, with an emphasis on the use of deixis, implicatures, presuppositions, and speech acts. The findings indicate that the use of personal and spatial deixis, hidden implicatures, presuppositions, as well as directive and commissive speech acts, is highly effective in capturing attention and driving purchases. Additionally, the study identifies “Directive Acts” as the dominant pragmatic category, with a total frequency of 38, indicating that directive actions (commands and instructions) are the most prevalent pragmatic strategy in direct selling on Tiktok Live. Language strategies such as creating urgency, personalizing interactions, and providing detailed product descriptions enhance viewer engagement. Positive viewer responses to various communication strategies underscore the success of direct sales campaigns. This research identified effective communication patterns in Tiktok Live ads and provides practical guidelines for sellers to enhance their communication skills on e-commerce platforms, thereby enriching linguistic pragmatic studies in the context of digital marketing.